2009
DOI: 10.5194/bg-6-1615-2009
|View full text |Cite
|
Sign up to set email alerts
|

After trees die: quantities and determinants of necromass across Amazonia

Abstract: Abstract. The Amazon basin, one of the most substantial biomass carbon pools on earth, is characterised by strong macroecological gradients in biomass, mortality rates, and wood density from west to east. These gradients could affect necromass stocks, but this has not yet been tested. This study aims to assess the stocks and determinants of necromass across Amazonian forests. Field-based and literature data were used to find relationships between necromass and possible determinants. Furthermore, a simple model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
44
3
23

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 41 publications
8
44
3
23
Order By: Relevance
“…Our current understanding suggests that CWD stocks generally decrease from north-eastern to south-western Amazonia (Baker et al 2007;Chao et al 2009a). Spatial variation in CWD stocks across the landscape may respond both to short-term climatic disturbances (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our current understanding suggests that CWD stocks generally decrease from north-eastern to south-western Amazonia (Baker et al 2007;Chao et al 2009a). Spatial variation in CWD stocks across the landscape may respond both to short-term climatic disturbances (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Kissing and Powers (2010), working in secondary forests in Costa Rica, showed strong positive correlations between stand age and the amount of CWD. Chao et al (2009a) working in mature forests in Amazonia showed that there was a relationship between forest structure and CWD, in particular with regard to biomass, wood density of living trees and mass of individual dead stems. Although these studies successfully associated CWD stocks with forest structure and dynamics, to our knowledge there has been no analysis of a potential effect of edaphic properties on CWD stocks.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations